ICTIOFAUNA ASOCIADA A LOS ARRECIFES CORALINOS HERMATIPICOS DE LA ENSENADA DE UTRIA, CHOCO, PACIFICO COLOMBIANO - Gómez D., Fabio; Museo Javeriano de Historia Natural ''Lorenzo Uribe, S.J., Departamento de Biología, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá (2013)
In the study ofthe Icthyofauna at the National Park Cove of Utria, are hundred one (101) fish species were found, belanging to 7 5 genera and 43 farnilies. They were collected and observated in fourreef system. With the method ofRapid Visual Census (RVC), a total of70 species were found at the four communities. With the additionals observation without visual count, 101 species were registrated, including sorne with criptic habits.